Development of LEBT and beam dynamics study in an initial RFQ part (input radio matcher) for a Heavy ion high current GSI-HSI-RFQ - Vorobyov, I.A.; Pershin, V.I.; Tretyakova, T.E.; Visotsky, S.A.; Yaramyshev, S.G.; Barth, W. (Вопросы атомной науки и техники, 2006)
Different variants of the LEBT for a Heavy Ion RFQ (GSI-UNILAC) were numerically investigated. The requirements for initial matching conditions for the RFQ structure have been defined. The optimization of an unmodulated input radio matcher (IRM) with a lowed slope of beam envelope was carried out with the use of the optimizing code ABC developed. The beam dynamics simulation with the use of the method of macroparticles was performed for the input radio matcher in comparison with the codes DYNAMION and PROTON. The comparison with data obtained from envelope equations and simulations was carried out.